AN EFFECT OF HALAL'S DIMENSIONS ON SUBSCRIPTION TO HALAL RESTAURANTS IN JAKARTA - Budiman, Andika Nuraga; Suyana, Hilma; Nurhayati, Ely (UNISSULA, 2022)
This research objective is to investigate the influence of Halal dimension towards subscribing Halal restaurant. This research objective is to investigate the influence of Halal dimension towards subscribing Halal restaurant. This research method was using questionnaire spread to 169 respondents in Central Jakarta area in Cempaka Putih. The purposive sampling with especially for Muslim was absolute condition to become this research samples. The result shows that interesting result that Muslim in Jakarta, which is we expecting these results are representing majority of population, evidently our respondents are not paying attention in Halal process before they visiting restaurant, which is one of the process is animal slaughtering process. An explanation of the relationship between Halal certification and subscribing. Halal restaurants have a significant relationship. apart from the regression results, the results of the T test have explained that the existence of Halal certification is very important. Also, Halal accreditation and their awareness need to be improve, there is not significant toward subscribing Halal restaurant. The main part is a religiosity which is a very strong religious status for Muslims; this is one of the reasons why Muslims always subscribe to restaurants because they believe wherever there is a religious status that is still firmly held.Â